Surface Perturbation Training to Prevent Falls in Older Adults: A Highly Pragmatic, Randomized Controlled Trial. Issue 7 (30th January 2020) - Lurie, Jon D; Zagaria, Alexandra B; Ellis, Lisa; Pidgeon, Dawna; Gill-Body, Kathleen M; Burke, Christina; Armbrust, Kurt; Cass, Sharil; Spratt, Kevin F; McDonough, Christine M
Abstract: Background: Falls are the leading cause of injuries among older adults, and trips and slips are major contributors to falls. Objective: The authors sought to compare the effectiveness of adding a component of surface perturbation training to usual gait/balance training for reducing falls and fall-related injury in high-risk older adults referred to physical therapy. Design: This was a multi-center, pragmatic, randomized, comparative effectiveness trial. Setting: Treatment took place within 8 outpatient physical therapy clinics. Patients: This study included 506 patients 65+ years of age at high fall risk referred for gait/balance training. Intervention: This trial evaluated surface perturbation treadmill training integrated into usual multimodal exercise-based balance training at the therapist's discretion versus usual multimodal exercise-based balance training alone. Measurements: Falls and injurious falls were assessed with a prospective daily fall diary, which was reviewed via telephone interview every 3 months for 1 year. A total of 211/253 (83%) patients randomized to perturbation training and 210/253 (83%) randomized to usual treatment provided data at 3-month follow-up. At 3 months, the perturbation training group had a significantly reduced chance of fall-related injury (5.7% versus 13.3%; relative risk 0.43) but no significant reduction in the risk of any fall (28% versus 37%, relative risk 0.78) compared with usual treatment. Time to first injurious fall showed reduced hazard in the first 3 months but no significant reduction when viewed over the entire first year. Limitations: The limitations of this trial included lack of blinding and variable application of interventions across patients based on pragmatic study design. Conclusion: The addition of some surface perturbation training to usual physical therapy significantly reduced injurious falls up to 3 months posttreatment. Further study is warranted to determine the optimal frequency, dose, progression, and duration of surface perturbation aimed at training postural responses for this population.